If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + -9) + 9 = 0 Reorder the terms: (-9 + 5x) + 9 = 0 Remove parenthesis around (-9 + 5x) -9 + 5x + 9 = 0 Reorder the terms: -9 + 9 + 5x = 0 Combine like terms: -9 + 9 = 0 0 + 5x = 0 5x = 0 Solving 5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '5'. x = 0 Simplifying x = 0
| 4q/5+6=188 | | y=(2e^2t)+4 | | -6v-6=-3(v+6) | | 4x^2-29+x^2-15+x^2+8=180 | | (18x+13)-7x= | | 2.5w-1,3w=14.4 | | 8x-1=6x+9 | | (x+7)=15 | | 3(x-5)+14(x+6)= | | 4(3x+12)+14x-13= | | 8(u+6)=-5u-17 | | 2.5w-1.3w=14.4 | | 9x+4+4x-5=90 | | (5x+12)+(8x-5)= | | 9v-43=2(v+3) | | w/15.36=6 | | (x-4)=13 | | -7x-87=-14x+39 | | 18x=48+12x | | -4*-4*-4=x | | 5x-10+2x+9=90 | | 4x1/12 | | 14.3-.4x=2.6+5.6 | | 5+2(3t-7)=3(2t+5)-24 | | f-1(30)=(4x-3)/2 | | 5x-10+2x+9=270 | | 7(4x+6)+11= | | 42a-22=-4(1-6a) | | -7*-7=x | | 7(4c+6)+11= | | 12x-1=6x+16 | | 3(x^2-1)=8x |